LITERASI KEUANGAN DAN LITERASI TEKNOLOGI BAGI PESANTREN KEWIRAUSAHAAN ISTANA MULIA ANYER - Atik Widayati; Jerry; Agung Dharmawan Buchdadi; Nabillah Hasna; Vina Pebianti (MUHKAL, 2023)
This article discusses increasing financial literacy and technology literacy among students and teachers at the Mulia Anyer Entrepreneurship Islamic Boarding School. The method developed is training with simulation which is preceded by an analysis of the condition of the activity participants. The simulation was carried out by giving a pre-test related to financial literacy and technology literacy to 30 participants consisting of students and teachers. The results of the simulation show that the level of financial and technological literacy of the students and teachers is still low. Therefore, a training was conducted entitled "Using Technology for Business". By participating in this training, they hope to be able to increase financial literacy and financial technology, and have an impact on good financial management and avoid various financial crimes.